Performance Analysis of Optimized Non-Linear Discrete PID MPPT for Efficient Battery Charging Incorporated with Grid - Ganguly, Anupama; Biswas, Pabitra Kumar; Adhikary, Sarasij; Acharya, Pradipta; Gupta, Suraj (2024 IEEE International Conference on Information Technology, Electronics and Intelligent Communication Systems (ICITEICS), 2024)
In power system networks, utilizing renewable energy resources has become more common within the past few years. Compared to several renewable sources like wind, geothermal, biomass, tidal etc, the solar proves to be the best choice because of its cleanliness and non-polluting nature. But to overcome its major shortcoming that is intermittency, it's a mandate to incorporate a storage device like battery, super capacitor, fuel cell etc. with the solar power generation. The development of a nonlinear discrete PID (NDPID)to be served as an MPPT controller for photovoltaic (PV) generation systems working in erratic climatic conditions is the subject of this article. The optimal NDPID gains which are found by Mountain Gazelle Optimization (MGO), help to drive the variable step of the conventional Perturb & Observe (Pb&O). In addition with, For optimal power control in the battery charging strategy, a PI controller, in association with grid accompanied by current governing topology, and a functional charging platform built with MGO-optimized NDPID-based rearrange able step size Pb&O to be acted as the efficient MPPT controller are implemented and verified in MATLAB/Simulink. Additionally, when compared to other current systems that have been studied in the literature, the introduced system as a whole demonstrates superior efficacy. Lastly, because grid integration is essential to the total demand, this suggested approach guarantees that the charging scheme is solely capable of delivering power even during erratic weather by sustaining the voltage of DC link.